If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-6+2j)=-2(2j-1)
We move all terms to the left:
3(-6+2j)-(-2(2j-1))=0
We add all the numbers together, and all the variables
3(2j-6)-(-2(2j-1))=0
We multiply parentheses
6j-(-2(2j-1))-18=0
We calculate terms in parentheses: -(-2(2j-1)), so:We get rid of parentheses
-2(2j-1)
We multiply parentheses
-4j+2
Back to the equation:
-(-4j+2)
6j+4j-2-18=0
We add all the numbers together, and all the variables
10j-20=0
We move all terms containing j to the left, all other terms to the right
10j=20
j=20/10
j=2
| 1/2x-10=22 | | 2(3x+8)=-28+2 | | r+8.1=-3.9 | | 3+6d=7+6+8d | | 7+4y=-5,y= | | 8x−5=10x−7 | | 6z-3z-1=2z+7 | | 8x-5=10x-78x−5=10x−7 | | 11/5y-3=-2 | | 11-4x-7-6=6 | | 24=33+x | | 12x-15=3(2x+13) | | x+16+x=21 | | -2(8-3h)=2(-6+4h) | | 20x+16=21 | | -5(2+3x)-4x=28 | | |x+2|=|2x+6|+1 | | -8g-1=-9g+9 | | 3(r−6)=9 | | 5(4x+9)=-26+51 | | 2g+2.6=18.6 | | 7.2=0.2m | | 4x+8=−1x−9 | | -19x—34=55—x | | 2p-4.2=1.8 | | 6(2x+6)-5=-5 | | 8n-5-1=-15+9n | | m-5.2/3=2.7 | | 17x+3⋅(x-1)=57 | | 1/2(2/3e-3+2e)=-4(1/8e+1-e) | | 56s^{2}+31s+3=0 | | 4(x+3)-9(x-2)=10 |